(untitled) (Bangladesh Rice Journal, 2023)
Groundwater recharge study is essential because it provides information on the groundwater flow and availability, and its sustainable management over many years. Groundwater recharge estimation also helps evaluating the characteristics of aquifer, such as its bearing capacity and susceptibility to contamination. Many studies so far have focused on several techniques and methods of estimation of groundwater recharge. These methods were very simple, such as seepage meter or tracer techniques, and even complex numerical modelling. However, picking up the right techniques from multiple require essential considerations such as physiography and climatic condition of the location, reliability of the technique, cost and resource availability, and other unavoidable factors that may put limitations in the applicability of a particular method. Furthermore, the reliability of a recharge estimation method also depends on the recharge rates of a particular site. Therefore, an appropriate technique of recharge estimation should be taken such that the estimation resolution of that technique is matched with the average recharge rates of that site. This paper discusses various recharge methods to select a suitable approach appropriate for the climatic condition of Bangladesh. Estimating groundwater recharge by only one method may result in several errors and draw a wrong conclusion. Applying multiple approaches can minimize these errors and enhance the acceptability of the recharge estimates. Bangladesh Rice J. 25 (2) : 45-56, 2021